ANALISIS PERSEPSI MAHASISWA TERHADAP KOMPETENSI DOSEN DALAM MENGAJAR PADA PROGRAM STUDI PAI FAKULTAS ILMU TARBIYAH DAN KEGURUAN UIN RADEN FATAH PALEMBANG - Nyayu Soraya (Tadrib: Jurnal Pendidikan Agama Islam, 2018)
Perception is one's ability to organize observations, such as: the ability to differentiate, the ability to group, and the ability to focus. Teachers' lesson is the unanimity of knowledge, honesty and attitudes of tangible action as an instructional agent that becomes one of the important factors to achieve the learning objectives and the other is one of the factors that are in the process of achieving the learning objectives and others. Education, teaching experience, and last teaching. Pedagogic competence is the ability of understanding of learners, planning and implementation of learning, evaluation of learning outcomes, and development of learners to actualize the various potentials it has. The pedagogic competence includes: Knowing the students, mastering theories about education, lesson materials, various techniques and learning methods, developing learning implementation plans (RPP) and evaluating the learning process and outcomes. Professional is a work or activity undertaken by a person and a living source of income that requires expertise, skill or skill that meets certain standards of quality or norm and requires professional education. Personality competence is a competence of qualities that appear from within and from the outside of the individual. And also a daily attitude of a lecturer towards students. Relate to the words, attitude in the face of students, behavior, language used and how to dress everyday. Social competence is a competence which is an intraction where the lecturer is required to be able to interact and communicate with learners, educators, parents and other members of the community.